Seltene Berufskrankheiten - Drexler, Hans (Internist, 2020)
Rare work-related illnesses do not usually meet the requirements to be recognised and compensated as a legal occupational disease. However, common diseases (e.g. ovarian carcinoma) are sometimes caused by occupational influences (e.g. asbestos), making the occupational disease ovarian cancer caused by occupational exposure to asbestos a rare disease. Since in our modern working world the occupational influences that are harmful to health are decreasing qualitatively (substitutes) and quantitatively (limit values), the diseases they cause are also becoming increasingly rare.
CRIS-Team WoS Importer:2020-05-08